Letter (copy) : International Solidarity Fund - goods sent to Spain - Tewson, Vincent
028-0158-001 Sch/PH./HVT/FC/212. Secretary's. 10th November, 1936. Mr. W. Schevenels, General Secretary, The International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS, VIIe. Dear Mr. Schevenels, INTERNATIONAL SOLIDARITY FUND - GOODS SENT TO SPAIN. I desire to thank you for your letter of the 9th instant giving detailed information as to the goods which have been sent to Spain through the medium of the International Solidarity Fund. This information will be very helpful to us in our publicity. PRESS STATEMENTS. As arranged with you on Friday last, I am enclosing copies of three press statements which were handed in by Dr. Adler. Yours, sincerely, Assistant Secretary. Press Statements. 292/946/28/158